ECONOMIC EFFECTS OF INTENSIFYING THE USE OF AGRICULTURAL INPUTS AND MODERN TECHNOLOGIES ON THE WHEAT PRODUCTIVITY IN IRAQ. - T. A. Gawad,; O. K. Jbara, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research aimed to illustrate the significant role of modern technology packages in agriculture, in particular in the growth of wheat cultivation. In this research will attempt to use O-Ring method. The purpose our using of this method is to prove that the modern technological packages used in agriculture, wheat cropping combined have a significant impact on increasing the productivity of the wheat crop in Iraq. A sample is taking from 290 farms, by divided into three governorates Namely Wasit, Babil and Diwaniyah. The packaging used to grow wheat was micronutrients, seeds, fertilizers, laser-level potassium sulphate, seeds, potassium sulphate fertilizers, Pallas herbicide, Atlantis herbicide and the farming cycle. All these elements were expressed; as A3i. This is an indicator of the intensification of agricultural inputs for developing wheat cultivation in Iraq. The results of the analysis showed that there is a high degree of correlation between each of the modern technological inputs and the rest of the modern inputs. The results also indicated that there is a growth and development in the productivity of the wheat crop because of the use of modern technologies, as there is a correlation between the use of the modern technology package and the development of the productivity of the wheat crop in Iraq.